2018
DOI: 10.1002/adom.201701272
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Nearly‐Hyperuniform Substrates by Tailored Disorder for Photonic Applications

Abstract: lithography, provide great flexibility but are slow and expensive, and are therefore not feasible. Conventional scalable techniques, for instance random etching processes such as chemical wet etching [3,4] or plasma dry etching, [5,6] operate in a small window of parameters, thus offering only limited freedom of design and the statistics of fabricated disordered interfaces is more or less fixed. Bottom up, self-organized colloid deposition is a promising candidate for scalable interface texturing. [7][8][9] Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 52 publications
3
61
0
Order By: Relevance
“…Robustness to positional variations of the scatterers is also expected, since random displacements do not seem to destroy hyperuniformity [48]. Together with the development of selfassembly processes able to produce hyperuniform architectures [49,50], the results in this article could guide the design of disordered correlated materials with blackbodylike absorption. The results should apply to all kinds of waves propagating in materials made of subwavelength absorbing scatterers in a non-absorbing host medium.…”
Section: Discussionmentioning
confidence: 86%
“…Robustness to positional variations of the scatterers is also expected, since random displacements do not seem to destroy hyperuniformity [48]. Together with the development of selfassembly processes able to produce hyperuniform architectures [49,50], the results in this article could guide the design of disordered correlated materials with blackbodylike absorption. The results should apply to all kinds of waves propagating in materials made of subwavelength absorbing scatterers in a non-absorbing host medium.…”
Section: Discussionmentioning
confidence: 86%
“…Disk positions were extracted from images of 104 × 70 μm 2 area via template matching, corresponding to about 2.000 Disks for the uncorrelated pattern and 16.000 for the most dense. [ 33,62 ] Briefly, the image of a sample particle was scanned over the original SEM image and tested for similarity at every point. Some disk pairs exhibit nominal surface‐to‐surface distances ≤0 nm (see e.g., Figure 3g) due to slight merging of the PMMA particles during tempering.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, it has been shown that the structure factor of dispersed colloidal particle (e.g. beads) patterns can be tuned by the ionic strength of the particular solvent 65,66 and that the dewetting of semiconductor layers leads to HUD patterns. 67 Also, soft-imprint conformal lithography has proven an excellent low-cost alternative to pattern large-areas with a resolution below 10 nm that could actually serve for both HUD holes and HUD network.…”
Section: Light Trapping Mechanism and Design Optimisationmentioning
confidence: 99%